From Overcrowded Prisons to Balanced Justice: Restorative Approaches in Criminal Law Reform - Sri Wulandari; Farisha Dian Prabaningtyas (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
Prison overcrowding has become a persistent challenge that undermines the legitimacy of criminal justice and generates widespread human rights violations. This paper examines the phenomenon as a structural crisis within criminal law rather than a mere administrative failure. Drawing on a normative juridical approach combined with comparative analysis, the study investigates how over-incarceration—particularly in Indonesia—reflects the limitations of retributive paradigms and explores restorative justice as a pathway toward balanced justice. Data from national and international sources, including the Directorate General of Corrections and the World Prison Brief, confirm that occupancy rates often exceed official capacity by 115–130 percent, resulting in conditions inconsistent with the International Covenant on Civil and Political Rights and the Nelson Mandela Rules. Comparative findings from New Zealand, Canada, and South Africa demonstrate that restorative justice can effectively reduce recidivism, alleviate overcrowding, and strengthen community trust. The results indicate that restorative justice not only provides alternatives to custodial sanctions but also aligns with human rights principles of dignity, fairness, and proportionality. The novelty of this research lies in reframing overcrowding as evidence of structural imbalance in criminal law and offering restorative mechanisms as a normative and practical solution. The study concludes that embedding restorative justice within criminal law reform is essential for achieving justice that is both effective and humane, with implications for Indonesia’s ongoing implementation of the 2023 Criminal Code.